Empowering Patients and Health Professionals in the Arab World: The King Abdullah bin Abdulaziz Arabic Health Encyclopedia on the Web - Altuwaijri, M. M. (Yearbook of Medical Informatics, 2011)
The purpose of this paper is to describe the needs and the process of establishing an online Arabic health encyclopedia to empower patients and health professionals with trustworthy information.A study was conducted by King Saud bin Abdulaziz University for Health Sciences in collaboration with Health on the Net (HON) Foundation to review the quality of Arabic health information on the internet. A review of health portals in other languages was performed. Meetings were conducted to investigate areas of collaboration with different stakeholders including: WHO, HON, the U.S. National Library of Medicine, and the NHS.The results of the assessment of Arabic health sites showed that a very small percentage (almost 4%) meets international standards. The study results call for immediate action to improve the trustworthiness of Arabic health information on the net. This will be achieved by establishing a reliable Arabic health encyclopedia and by encouraging health professionals from all Arab countries to contribute to its creation. It is important for the 300 million Arabic citizens around the world to be able to access valuable health information on the internet.More than 300 million Arab citizens around the world have missed the opportunity to use the internet to provide them with quality health information. Hence, to bridge this gap, a new project was launched to develop an online Arabic health encyclopedia. Moreover, this study proposes an Arabic health information foundation be established to govern and accredit the Arabic health websites, and to work in collaboration with HON, to regulate and promote the quality of health information on the internet in Arab countries.
Keywords: Internet; health information seeking; personal health; consumer health; health encyclopedia